Answer: The equation is y=k(x). So 12=k(5), divide by 5 on both sides coming up with k=2.4. Plug 2.4 in as k in the original equation, making it 30=2.4(x), divide both sides by 2.4, 30 divided by 2.4 is 12.5, making x=12.5
Read more on Brainly.com - brainly.com/question/1756486#readmore
Step-by-step explanation:
The ratio of the radius of the smaller watch face to the radius of the larger watch face is 4:5.
The area of the circle is given by the formula,
As we know that the ratio of the area of the two watches is 16:25. And we also know that the area of a circle is given by the formula,
Now, as we know that the ratio of the area of the watches can be written as,
Hence, the ratio of the radius of the smaller watch face to the radius of the larger watch face is 4:5.
Learn more about Circle:
Answer:
4:5
Step-by-step explanation:
Let r be the radius of small watch
Area of small watch=π
Let R be radius of larger watch= π
Area of larger watch= π
It is given that the ratio of their areas= 16:25
=
π: π= 16:25
=
r:R= 4:5
Hence, the ratio of their radii= 4:5
Hence, the correct answer is 4:5
(length of the foot) = 0.860 • (length of the forearm) + 3.302
If you let y = length of the foot and x = length of the forearm, this equation can be simplified to
y = 0.860x + 3.302.
Using this equation, how long would the foot of a person be if his forearm was 17 inches long?
B. What is the rate of change of the equation from Part A?
Compare the equation from Part A to your data. Are they the same? Which has a greater rate of change? Why do you think the values are different?
C. Is the relation in your data a function? Why or why not? Could the equation in Part A represent a function? Why or why not? Explain your answer.
Step-by-step explanation:
Part A:
y=0.860x + 3.302
y= 0.860(17) + 3.302
y= 14.62 + 3.302
y= 17.922
Part B:
step 1
y=0.860x + 3.302
y= 0.860(17) + 3.302
y= 14.62 + 3.302
y= 17.922
step 2
y=0.860x + 3.302
y= 0.860(18) + 3.302
y= 15.48 + 3.302
y= 18.782
step 3
18.782-17.922=.86
So, the rate of change is .86
Hope it helps!!
Answer:
b= -3
Step-by-step explanation:
y=x²/4+bx+10=1/4(x²+2*2b+4b²)+10-b²
=(1/4'x+2b)²+10-b²
==>-2b=6==>b=-3
mark brainliest :)